"I Know Down to My Ribs": A Narrative Research Study on the Embodied Adult Learning of Creative Writers. (August 2015) - Tobin, Jennifer A.; Tisdell, Elizabeth J.
This article reports the findings of a qualitative study that used narrative analysis to explore the role of embodied learning in the writing processes of creative writers. From a theoretical framework that draws on Merleau-Ponty's philosophy of the body, Gendlin's concepts of felt sense and focusing, and Jordi's analysis of reflection for integrating mind and body, this study highlights one participant's narrative and then discusses primary themes that emerged across narratives. Findings revealed a history of encouragement to write, writing that was used for healing, and an expanded sense of body awareness that encouraged flow in the writing process.